Fusiones y adquisiciones en Latinoamérica, gobierno corporativo y modelo gravitacional - Vasco, Mateo (2014)
In this study, and by making use of a gravity model, an analysis is made on whether transnational mergers and acquisitions (M&A) are influenced by the corporate governance standards of a country. The study only focuses on the M&A flows from the OECD countries towards Latinamerican economies, as well as using the Kaufmann indicators for measuring, among others, the corporate governance of a country. Evidence is found that the gravity model is explicative of the M&A flows, and that the better the level of corporate governance at both origin and destination countries, the greater is the M&As activity.